A study of the growth-time effect on graphene layer number based on a Cu–Ni bilayer catalyst system. Issue 28 (1st March 2016) - Wu, Tao; Liu, Zhiduo; Chen, Guoxin; Dai, Dan; Sun, Hongyan; Dai, Wen; Jiang, Nan; Jiang, Ye Hua; Lin, Cheng-Te
Abstract : Graphene layer number is controlled by changing Cu–Ni ratio and growth time. Single- and few-layer graphene are formed separately on Cu- and Ni-rich catalysts. The growth of bilayer graphene is attributed to the synergic effect of Cu and Ni (1 : 1). Abstract : The evolution of graphene-based electronic, optoelectronic, and sensing devices has grown at a fast pace in the recent decade, due to the rapid development of manufacturing technology for high-quality graphene. However, the absence of controllability of graphene thickness sets an additional barrier for device applications. Here, we demonstrate that the number of graphene layers can be well controlled by adjusting the Cu–Ni catalyst composition and the reaction time. The Cu–Ni bilayer catalysts are prepared by sputtering Ni and then Cu films on a SiO2 /Si substrate with various film thicknesses. With the increase of the growth time, single-layer graphene would be formed on the Cu-rich catalysts, whereas bilayer to few-layer graphene can be obtained on the Ni-rich films. In addition, the formation of single-layer to bilayer graphene as a function of time is attributed to the synergic effect of Cu and Ni catalysts with 1 : 1 composition. The precise control of graphene layer number enables the further development of advanced electronics and sensors.